2005
DOI: 10.1103/physrevlett.94.047202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field Induced Transition to the1/2Magnetization Plateau State in the Geometrically Frustrated MagnetCdCr

Abstract: The magnetization of the geometrically frustrated spinel CdCr2O4 was measured in pulsed fields of up to 47 T. We found a metamagnetic transition to a very wide magnetization plateau state with one half of the full moment of S=3/2 Cr3+ at 28 T, independent of the field direction. This is the first observation of magnetization plateau state realized in Heisenberg pyrochlore magnet. The plateau state can be ascribed to a collinear spin configuration with three-up and one-down spins out of four spins of each Cr te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
164
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(180 citation statements)
references
References 24 publications
15
164
1
Order By: Relevance
“…Previous studies have shown that spin-lattice coupling can lift the ground state degeneracy in frustrated magnets [11][12][13][14][15][16][17] . However, the detailed microscopic mechanism, i.e.…”
Section: (C) Shows That At 32 K (T < T N ) For H < 10mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that spin-lattice coupling can lift the ground state degeneracy in frustrated magnets [11][12][13][14][15][16][17] . However, the detailed microscopic mechanism, i.e.…”
Section: (C) Shows That At 32 K (T < T N ) For H < 10mentioning
confidence: 99%
“…For CdCr 2 O 4 with  CW = -88 K, the half-magnetization plateau phase occurs for H > 28 Tesla. 12 For HgCr 2 O 4 with  CW = -32 K, on the other hand, the half-magnetization plateau phase occurs for 10 Tesla < H < 28 Tesla and the full magnetization plateau phase for H > 40 Tesla. 13 The hysteretic nature of the fieldinduced transitions is observed with ramping down the field, indicating that the transitions are of first order.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lattice distortion can occur in different forms, depending on details of the crystal environment: tetragonal I4m2 symmetry for ZnCr 2 O 4 [33], tetragonal I4 1 /amd for CdCr 2 O 4 [33], and orthorhombic F ddd for HgCr 2 O 4 [26,34]. When an external magnetic field is applied to the Neél state, the half-magnetization plateau states appear in CdCr 2 O 4 [35] and HgCr 2 O 4 [26,34] due to the field-induced lattice instability [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…This quasi-elastic magnetic scattering becomes gapped within the low temperature tetragonal phase of ZnCr 2 O 4 , drawing similarities to spin-Peierls physics, albeit in three dimensional materials. Other spinels exhibit unexpected plateaus in their magnetization as a function of field at low temperature which have been of intense interest [19,20]. Such magnetization plateaus have been modeled with biquadratic exchange terms in the effective spin Hamiltonian of these materials, arising from strong magneto-elastic coupling [21].…”
mentioning
confidence: 99%